Evaluation of the Management of Pharmaceutical Preparations at the Batunadua Padangsidimpuan Community Health Center in 2023 - mayasari, Dini; Diningsih, Ayus; Ritonga, Nefonavratilova (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2024)
Management of pharmaceutical preparations through pharmaceutical services at community health centers includes several activities, namely planning, procurement, receiving, storage, distribution and control. The aim of this research is to find out the mechanism for managing pharmaceutical preparations at the Batunadua Community Health Center. This research uses an observational descriptive method. The population and sample in this study is all drug management data which includes planning, procurement, receipt, storage, distribution and control of the Batunadua Community Health Center in 2023. The place and time of the research was at the Batunadua Community Health Center, Padangsidimpuan City in May-June 2024. The instruments used were observation checklist sheet and interview sheet. The results obtained from this research are the planning stage with 100% results, procurement with 100% results, receipt with 100% results, storage with 80% results, distribution with 100% results and control with 100% results. The conclusion of this research is that the management of pharmaceutical preparations at the Batunadua Community Health Center is in accordance with Minister of Health Regulation no. 74 of 2016.